Taxonomic notes on Artemisia waltonii (Asteraceae, Anthemideae), with reduction of A. kangmarensis and A. conaensis to the synonymy of its type variety - Guo, Xin-Qiang; Wang, Long; Yang, Qin-Er (Phytotaxa, 2020)
Based on observations on both herbarium specimens (including type material) and living wild plants, we demonstrate that Artemisia waltonii var. waltonii (Asteraceae, Anthemideae) is readily distinguishable from A. waltonii var. yushuensis by having abaxially tomentose (vs. glabrescent, rarely sparsely pubescent) leaves. The type variety is distributed only in central and southern Xizang (Tibet) in China whereas the latter one occurs widely in southern Qinghai, western Sichuan and eastern Xizang in the country. Moreover, we determine that A. conaensis and A. kangmarensis, both described from Xizang, are identical with A. waltonii var. waltonii and thus should be synonymized. Lectotypification is proposed for A. waltonii.